PENGARUH STRATEGI PEMBELAJARAN KOOPERATIF BERBANTUAN MEDIA ALFABET CARD TERHADAP MEMBACA PERMULAAN SISWA KELAS II SD INPRES 5/81 BULU-BULU - DH, Satriani; Rukayah; Firman, Alif Batara (MACCA : Science-Edu Journal, 2025)
This research is a quantitative type of experimental research which aims to determine the significant influence on students' initial reading abilities before and after using Alphabet Card media through cooperative learning strategies. The research design used was one group Pretest-Posttest design. The population in this study were all class II students at SD Inpres 5/81 Bulu-Bulu with a sample of 30 students selected using a saturated sampling technique. The data collection technique used was an initial reading test to determine students' initial reading abilities before and after using Alphabet Card media through cooperative learning strategies. The data analysis techniques used are descriptive and inferential statistical analysis techniques. Based on the results of descriptive statistical analysis, it was found that the Pretest score for students' initial reading ability was in the poor category and the Posttest score for students' initial reading ability was in the good category. Based on the results of inferential statistical analysis using the paired samples test, it shows that the significance value is 0.000 > 0.05, which means there is a significant difference in students' initial reading abilities before and after using the cooperative learning strategy type assisted by Alphabet Card media for class II students at SD Inpres 5/81 Bulu-Bulu. The conclusion of this research is that there is an influence of using Alphabet Card media through cooperative learning strategies on the beginning reading ability of class II students at SD Inpres 5/81 Bulu-Bulu.